The fundamentalist mindset: psychological perspectives on religion, violence, and history - Strozier, Charles B. (Oxford University Press, 2010)
Foreword / Martin E. Marty -- Introduction / Charles B. Strozier and David M. Terman -- Part I: What is the fundamentalist mindset? -- Definitions and dualisms / Charles B. Strozier and Katharine Boyd -- Theories of group psychology, paranoia, and rage / David M. Terman -- The apocalyptic / Charles B. Strozier and Katharine Boyd -- The charismatic leader and the totalism of conversion / Charles B. Strozier, Katharine Boyd, and James W. Jones -- Part II: Motivations for violence -- The paranoid gestalt / David M. Terman -- The apocalyptic other / Charles B. Strozier -- The social psychology of humiliation and revenge : the origins of the fundamentalist mindset / Bettina Muenster and David Lotto -- Fundamentalist faith states : affect regulation and the attachment relationship to God / Daniel Hill -- Part III: Christian and American contexts -- Eternal warfare : violence on the mind of American apocalyptic Christianity / James W. Jones -- Opening the seven seals of fundamentalism / Charles B. Strozier -- The unsettling of the fundamentalist mindset : shifts in apocalyptic belief in contemporary conservative Christianity / Lee Quinby -- Part IV: Global and historical contexts -- Motivations for jihadi violence / Farhad Khosrokhavar -- Ordering chaos : Nazi millennialism and the quest for meaning / David Redles -- The French Revolution and the paranoid gestalt / David P. Jordan -- Hindu victimhood and India's Muslim minority / John R. McLane -- Conclusion: A fundamentalist mindset / James W. Jones